Women in Surgery Events Alone do not Change Medical Student Perceptions of Gender Bias and Discrimination in Orthopaedic Surgery - Hull, Bethany; Pestrin, Olivia; Brennan, Caitlin M.; Hackney, Rosie; Scott, Chloe E.H. (Frontiers in Surgery, 2022)
Aims: This study investigated the perceptions of medical students regarding the barriers to pursuing a career in trauma and orthopaedics (T&O); and whether these perceptions were altered by attending an event promoting women in T&O. Methods: An event consisting of presentations and interactive sessions from two female T&O trainees was hosted online. Attendees completed pre and post-event questionnaires. Students were asked about their previous exposure to T&O, perceptions of gender imbalances in T&O and what barriers they perceived prevented women from entering T&O. Univariate analysis was performed to identify changes in perceptions following the event. Results: Pre-event questionnaires were completed by 102 people; and post-event by 52. Although 64/102 respondents were considering a career in T&O, 26/102 were dissuaded by perceived gender disparities. Perceptions of gender disparities were significantly higher in UK based attendees compared to other nationalities (p=0.047). Attendees were more likely to want to pursue a career in T&O if they had been directly exposed at medical school (p=0.044), but exposure did not alter perceptions of women in T&O. The most common perceived barrier was the orthopaedic stereotype followed by male dominated workplace culture, and lack of female role models. Pre and post-event responses did not differ significantly for any areas examined. Conclusion: There are significant concerns amongst medical students regarding gender based discrimination within T&O, and these perceptions were not altered by attending a one-off women in T&O event. Early exposure to T&O appears important to improve interest in orthopaedics, whereas negative stereotyping is a barrier.